Tumor Exosome Mimicking Nanoparticles for Tumor Combinatorial Chemo-Photothermal Therapy - Tian, Ran; Wang, Zhaosong; Niu, Ruifang; Wang, Hanjie; Guan, Weijiang; Chang, Jin (Frontiers in Bioengineering and Biotechnology, 2020)
The development of biomimetic nanoparticles with functionalities of natural biomaterial remains a major challenge in cancer combination therapy. Herein, we developed a tumor-cell-derived exosome-camouflaged porous silicon nanoparticles (E-MSNs) as a drug delivery system for co-loading ICG and DOX (ID@E-MSNs), achieving the synergistic effects of chemotherapy and photothermal therapy against breast cancer. Compared with ID@MSNs, the biomimetic nanoparticles ID@E-MSNs can be effectively taken up by the tumor cell and enhance tumor accumulation with the help of the exosome membrane. ID@E-MSNs also retain the photothermal effect of ICG and cytotoxicity of DOX. Under 808 nm near infrared irradiation, ICG can produce hyperthermia to collapse E-MSNs nanovehicles, accelerate drug release, and induce tumor ablation, achieving effective chemo-photothermal therapy. In vivo results of 4T1 tumor-bearing BALB/c mice showed that ID@E-MSNs could accumulate tumor tissue and inhibit the growth and metastasis of tumor. Thus, tumor exosome-biomimetic nanoparticles indicate a proof-of-concept as a promising drug delivery system for efficient cancer combination therapy.